Effects of salinity on the Macro- and Micronutrient contents of a Halophytic Plant Species (Portulaca oleracea L.) - Bekmirzaev, Gulom (2021)
The main purpose of the two consecutive experimental studies presented here was to compare the effect of salinity on nutrients in leaves of the halophytic plant species Portulaca oleracea L. and in soil. The first experiment was conducted to study the effect of salinity on plant growth, biomass accumulation, yield, root layer development, salt accumulation, and the dynamics of changes in mineral substances in plants and soil. In the second experiment, P. oleracea seeds were sown directly into salinized soil (treated immediately before plant growth) to determine the nutrient levels in leaves and soil. Three salinity treatments (saline water solution with NaCl: T1, 5 dS m−1 ; T2, 9.8 dS m−1 ; and T3, 20 dS m−1 ) and a control treatment (T0, 1 dS m−1 ) were used in the first experiment. The soil in the second experiment was used in a previous study (performed immediately before P. oleracea growth) (salinized soil: T1, 7.2 dS m−1 ; T2, 8.8 dS m−1 ; T3, 15.6 dS m−1 ; T0, 1.9 dS m−1 ). The plants were irrigated with tap water at amounts in the range of 0.25–0.50 L/pot. Analysis of the experimental results showed that P. oleracea is resistant to salinity, is able to remove ions (400–500 kg ha−1 NaCl), and can be grown in saline soil. The results indicated that P. oleracea is able to grow in high-salinity soil. This finding was confirmed by the dry matter obtained under high-salinity conditions. Salinity stress affected nutrient uptake in leaves and soil.